2016
DOI: 10.1007/s10096-015-2549-9
|View full text |Cite
|
Sign up to set email alerts
|

First recurrence of Clostridium difficile infection: clinical relevance, risk factors, and prognosis

Abstract: Therapy for recurrent Clostridium difficile-associated diarrhea (CDAD) is challenging. We evaluated the frequency, associated risk factors, and prognosis of first CDAD recurrences. Prospective cohort study of all consecutive cases of primary CDAD diagnosed in a university hospital from January 2006 to June 2013. Recurrent infection was defined as reappearance of symptoms within 8 weeks of the primary diagnosis, provided that CDAD symptoms had previously resolved and a new toxin test was positive. Predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…The risk of colectomy and the mortality risk in patients requiring colectomy were based on a prospective cohort Spanish study [ 26 ], whose aim was to evaluate the frequency, associated risk factors and prognosis of first CDAD recurrences, and a literature review [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The risk of colectomy and the mortality risk in patients requiring colectomy were based on a prospective cohort Spanish study [ 26 ], whose aim was to evaluate the frequency, associated risk factors and prognosis of first CDAD recurrences, and a literature review [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies greatly support these previous results, but also name additional risk factors for recurrent CDI not mentioned by any of the current guidelines. In a retrospective, but very extensive cohort, steroid treatment was found to be associated with recurrent CDI [ 79 ], and a very recent prospective cohort identified enteral tube nutrition as another independent predictor of recurrence [ 80 ]. In another report on a retrospective cohort of more than 750 patients, the authors found a longer hospital stay to independently predict recurrent CDI [ 81 ], and there is growing evidence that inflammatory bowel disease may also predispose to CDI recurrence [ 82 ].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…In the European EU-CLID study, that followed the methodogy of the Spanish Studies, the mean number of CDI episodes was of 7 episodes of CDI per 10,000 patient-bed days and it was estimated that 23% of the cases were missed [12]. Most cases described in Spain have mild or moderate severity, are health care-associated, and have a recurrence frequency ranging from 12% to 18% [6,11,13].…”
Section: Introductionmentioning
confidence: 99%